(untitled) (The Pakistan Development Review, 1999)
Rapid changes in prices are of concern in almost all countries since the 1970s. However, the issue is of serious concern in developing countries where imported inflation is seen to be driving domestic inflation resulting in limited effectiveness of domestic policies to control inflation. Like most developing countries, in Pakistan also, the domestic price level started rising from the mid-1970s. The exchange rate started depreciating continuously from the early 1980s.1 Continuous devaluation of currency and inflation in the 1980s seems to suggest a correlation between the two variables. The empirical studies, like Rana and Dowling (1983) suggest that foreign inflation was the most significant factor in explaining changes in the domestic price level in nine Asian less developed countries during 1973-79. This suggests that, while, these countries could do little to control inflation, the policies of other countries, particularly their major trading partners, had a significant impact on their domestic prices. A simultaneous relationship between the inflation rate and the exchange rate changes is viewed by certain researchers to exist. [Cooper (1971) and Krugman and Taylor (1978).]